Pengaruh Penambahan Ubi Jalar Cilembu (Ipomoea batatas (L). Lam cv. Cilembu) Terhadap Nilai Gizi dan Sifat Sensoris Dodol Ketan - Naibaho, Melda Yanti; Kencana Putra, I Nengah; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 1 (2024): Jurnal ITEPA, 2024)
Sticky rice dodol is a traditional food that has a sweet taste and chewy texture, but low in fiber and vitamins. The addition of Cilembu sweet potatoes, which have high nutritional content, is expected to complement the nutritional value of sticky rice dodol. This study aimed to find out the effect of the addition of Cilembu sweet potatoes on the nutritional value and sensory properties of sticky rice dodol, and to determine the optimal addition of Cilembu sweet potatoes in order to produce sticky rice dodol with the best nutritional value and sensory properties. The experimental design used in this study was a Completely Randomized Design, with the treatment of the addition of Cilembu sweet potatoes consisting of 6 levels: 0%, 10%, 20%, 30%, 40%, and 50%. The treatment was repeated 3 times, resulting in 18 experimental units. The data obtained were analyzed by analysis of variance, and if the treatment had a significant effect, then it was further analyzed with the Duncan Multiple Range Test. The result showed that the treatment of Cilembu sweet potatoes addition had a significant effect on moisture content, ash, protein, carbohydrate, crude fiber, ?-carotene, color, texture, taste, and overall reception, but had no significant effect on fat content and aroma. The addition of Cilembu sweet potatoes at 30% produced the best characteristic, with a water content of 25,84%, ash content of 1,52%, protein content of 9,10%, fat content of 6,10%, carbohydrate content of 57,44%, crude fiber content of 4,45%, ?-carotene content of 898,84mg/100g, yellowish brown color, chewy texture, no Cilembu sweet potato aroma, sweet taste, and overall acceptance of “liked”. Keywords: Cilembu sweet potatoes, nutritional value, sticky rice dodol